2022
DOI: 10.60072/ijeissah.2022.v1i01.007
|View full text |Cite
|
Sign up to set email alerts
|

Challenges of Online Modules for Task-Based Learning of Mathematics for Effective Online Teaching-Learning Process

Abstract: The COVID-19 pandemic caused a sudden shut down of educational institutions, which resulted in learning challenges among the students as the education medium switched to online mode. Mathematics learning based on online modules tasks is challenging for the students due to its complexity.Therefore, thisstudy aims to elaborate challenges of online modules for task-based mathematics learning for an effective online teaching-learning process. In particular, this study explores the chall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Learners rely on keywords to solve the MWPs and this often leads to incorrect translations (Salemeh & Etchells, 2016). Research has investigated the teaching-learning of mathematics online (Upadhyay & Mohammed, 2022) and examined the teacher's perceptions of flipped classroom approach towards digital literacy skills trying to help in promoting teaching-learning mathematics (Eriyagama & Mohammed, 2024), however not examined the techniques of Math word problems. Previous local research findings have found that students are generally weak in solving Math word problems, especially in problems that required skills in choosing the various Mathematical techniques they have learned in previous years.…”
Section: Problem Statementmentioning
confidence: 99%
“…Learners rely on keywords to solve the MWPs and this often leads to incorrect translations (Salemeh & Etchells, 2016). Research has investigated the teaching-learning of mathematics online (Upadhyay & Mohammed, 2022) and examined the teacher's perceptions of flipped classroom approach towards digital literacy skills trying to help in promoting teaching-learning mathematics (Eriyagama & Mohammed, 2024), however not examined the techniques of Math word problems. Previous local research findings have found that students are generally weak in solving Math word problems, especially in problems that required skills in choosing the various Mathematical techniques they have learned in previous years.…”
Section: Problem Statementmentioning
confidence: 99%
“…With the surge of technology in educational practice due to a new paradigm, the development of skills in digital literacy has grown more important in the learning and teaching process (Upadhyay & Mohammed, 2022). In brief, digital literacy is the ability to interpret and apply information in a variety of formats from a variety of sources when delivered via computer ethically and responsibly (Gister, 1997).…”
Section: Introductionmentioning
confidence: 99%